High-strength wave-absorbing copper mesh material and preparation method thereof

By adjusting the component ratio and preparation process of copper wire, the strength of copper mesh material is improved, the stability of copper mesh material in mechanical stress environment is solved, and the stability of wave absorption effect is ensured.

CN119553133APending Publication Date: 2025-03-04HEBEI WEIJIA METAL MESH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411726445.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The copper wires of existing copper mesh materials are low in strength and cannot be maintained stable in an environment that withstands mechanical stress, which affects the stability of the wave absorption effect.

Method used

By reasonably adjusting the component ratio of the copper wire, adding elements such as Sn, Al, B, Cr, Ni and Zn, and preparing copper wire through steps such as smelting, casting, forging, rolling, heat treatment and drawing, to improve its strength.

Benefits of technology

It significantly improves the strength of the copper wire, solves the deformation and damage problems of copper mesh materials under mechanical stress environment, and ensures the stability of the wave absorption effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of metal nets, and provides a high-strength wave-absorbing copper net material and a preparation method thereof.The copper net material is formed by weaving copper wires, and the copper wires are composed of, by weight, 0.2%-0.6% of Sn, 0.06%-0.24% of Al, 0.03%-0.135% of B, 0.14%-0.24% of Cr, 0.12%-0.18% of Ni, 0.14%-0.2% of Zn and the balance Cu and inevitable impurities. According to the technical scheme, the problem that the copper wire of a copper wire mesh material is low in strength in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal meshes, and in particular to a high-strength wave-absorbing copper mesh material and a preparation method thereof. Background Art

[0002] With the rapid development of modern electronic technology, electronic equipment has been widely and deeply used in many fields such as military, communication, aerospace, and medical. When these devices are running, a large number of electromagnetic waves will be generated. At the same time, they are also very susceptible to interference from external electromagnetic waves. This electromagnetic interference problem seriously affects the normal operation and performance of the equipment. In order to solve this problem, absorbing materials came into being.

[0003] Copper mesh has a wide range of applications in the field of wave absorption, thanks to its ability to efficiently sense and conduct electromagnetic waves, and its good machinability, light transmittance and air permeability, and can be cut, bent and other operations according to actual needs. However, copper is a relatively soft metal, and its crystal structure characteristics determine its low strength. In some environments that need to withstand mechanical stress, such as the surface of a high-speed flying aircraft, or the inside of an electronic device with continuous vibration, this low-strength copper mesh exposes obvious disadvantages. Because it cannot withstand these external forces, the copper mesh is prone to deformation and breakage, which will seriously affect the stability of the wave absorption effect and cannot meet the requirements of practical applications. Therefore, it is urgent to develop a high-strength wave-absorbing copper mesh material. Summary of the invention

[0004] The invention provides a high-strength wave-absorbing copper mesh material and a preparation method thereof, which solves the problem of low strength of copper wires of the copper mesh material in the related art.

[0005] The technical solution of the present invention is as follows: The invention provides a high-strength absorbing copper mesh material, which is woven from copper wires. The copper wires are composed of the following components in weight percentage: Sn 0.2%-0.6%, Al 0.06%-0.24%, B 0.03%-0.135%, Cr 0.14%-0.24%, Ni 0.12%-0.18%, Zn 0.14%-0.2%, and the rest are Cu and inevitable impurities.

[0006] As a further technical solution, the weight ratio of the sum of the weights of Al and B to the weight of Cr is 1≤(Al+2B) / Cr≤2.

[0007] In the present invention, when the weight ratio of the sum of the weights of Al and B to Cr is 1≤(Al+2B) / Cr≤2, it helps to further improve the strength of the copper wire.

[0008] As a further technical solution, the weight ratio of the Al to the B is Al / B>2.

[0009] In the present invention, when the weight ratio of the sum of the weights of Al and B to Cr is 1≤(Al+2B) / Cr≤2 and Al / B>2, the strength of the copper wire can be further improved.

[0010] The present invention also proposes a method for preparing the high-strength microwave-absorbing copper mesh material, comprising the following steps: S1, smelting: weighing raw materials according to the components in weight percentage, smelting, and obtaining copper liquid; S2, casting: the copper liquid is cast to obtain a copper ingot; S3, wire forming: the copper ingot is forged, rolled, heat treated and drawn to obtain copper wire; S4, weaving: the copper wires are weaved to obtain a copper mesh material.

[0011] As a further technical solution, in step S1, during the smelting, the temperature is 1200-1250° C. and the time is 10-20 min.

[0012] As a further technical solution, in step S3, the temperature during the rolling is 680-850°C.

[0013] In the present invention, by reasonably adjusting the temperature during rolling, defects inside the material caused by processing stress during the processing are avoided.

[0014] As a further technical solution, in step S3, the heat treatment includes a first stage heat treatment and a second stage heat treatment; During the first stage of heat treatment, the holding temperature is 900-950°C for 1-2 hours. After the holding is completed, the material is cooled to room temperature at a cooling rate of 12-16°C / s. During the second stage heat treatment, the holding temperature is 450-500°C, the holding time is 1-2h, and after the holding is completed, it is cooled to room temperature at a cooling rate of 4-8°C / s.

[0015] In the present invention, the heat treatment includes a first stage heat treatment and a second stage heat treatment. By optimizing the holding temperature and holding time during the two stages of heat treatment, especially matching a reasonable cooling rate, the strength of the copper wire is further improved.

[0016] As a further technical solution, in step S3, the wire diameter of the copper wire is 0.025~0.1mm.

[0017] As a further technical solution, in step S4, the weaving is performed in a plain weave or a twill weave.

[0018] As a further technical solution, in step S4, after the weaving, rolling is also included.

[0019] As a further technical solution, in step S4, the mesh size of the copper mesh material is 80-400 meshes and the thickness is 0.05-0.23 mm.

[0020] The working principle and beneficial effects of the present invention are: In the present invention, elements such as Sn, Al, B, Cr, Ni and Zn are used as alloying elements of the copper wire, and the components of the copper wire are optimized to make the copper wire have higher strength, thereby solving the problem of low strength of the copper wire of the copper mesh material in the related art. In particular, the strength of the copper wire is improved by combining the elements of Al, B and Cr and adjusting the content range thereof. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] In the following examples and comparative examples, the tin content in the tin-copper is 10 wt %; the chromium content in the chromium-copper is 0.9 wt %; the nickel content in the nickel-copper is 30 wt %; and the zinc content in the zinc-copper is 80 wt %.

[0023] Example 1 A method for preparing a high-strength microwave-absorbing copper mesh material comprises the following steps: S1. Smelting: according to the target composition of the copper wire, tin copper, pure aluminum, elemental boron powder, chromium copper, nickel copper, zinc copper and pure copper are weighed, and smelted at 1250° C. for 10 min to obtain copper liquid; S2, casting: After the copper liquid is cast, a copper ingot is obtained; S3, wire forming: after forging, rolling, heat treatment and drawing, the copper ingot is obtained into a copper wire with a wire diameter of 0.1 mm; Among them, during rolling, the temperature is 680℃; During heat treatment, the holding temperature is 700°C and the holding time is 2h. After the holding is completed, it is cooled to room temperature at a cooling rate of 10°C / s; S4, weaving: the copper wire is woven to obtain a copper mesh material; Among them, plain weave is adopted, the mesh number of the copper mesh material is 80 mesh and the thickness is 0.23mm; The copper wire is composed of the following components in weight percentage: Sn 0.2%, Al 0.06%, B 0.03%, Cr 0.14%, Ni 0.12%, Zn 0.14%, and the rest is Cu and inevitable impurities.

[0024] Example 2 A method for preparing a high-strength microwave-absorbing copper mesh material comprises the following steps: S1. Smelting: according to the target composition of the copper wire, tin copper, pure aluminum, elemental boron powder, chromium copper, nickel copper, zinc copper and pure copper are weighed, and smelted at 1200° C. for 20 min to obtain copper liquid; S2, casting: After the copper liquid is cast, a copper ingot is obtained; S3, wire forming: after forging, rolling, heat treatment and drawing, the copper ingot is obtained into a copper wire with a wire diameter of 0.025 mm; Among them, during rolling, the temperature is 850℃; During heat treatment, the holding temperature is 700°C and the holding time is 4h. After the holding is completed, it is cooled to room temperature at a cooling rate of 10°C / s; S4, weaving: after the copper wire is woven, it is rolled to obtain a copper mesh material; Among them, plain weave is adopted, the mesh number of the copper mesh material is 400 mesh, and the thickness after rolling is 0.05mm; The copper wire is composed of the following components in weight percentage: Sn 0.6%, Al 0.24%, B 0.135%, Cr 0.24%, Ni 0.18%, Zn 0.2%, and the rest is Cu and inevitable impurities.

[0025] Example 3 A method for preparing a high-strength microwave-absorbing copper mesh material comprises the following steps: S1. Smelting: according to the target composition of the copper wire, tin copper, pure aluminum, elemental boron powder, chromium copper, nickel copper, zinc copper and pure copper are weighed, and smelted at 1200° C. for 20 min to obtain copper liquid; S2, casting: After the copper liquid is cast, a copper ingot is obtained; S3, wire forming: after forging, rolling, heat treatment and drawing, the copper ingot is obtained into a copper wire with a wire diameter of 0.05 mm; Among them, during rolling, the temperature is 800℃; During the heat treatment, the holding temperature is 700°C and the holding time is 3h. After the holding is completed, it is cooled to room temperature at a cooling rate of 10°C / s; S4, weaving: the copper wire is woven to obtain a copper mesh material; Among them, plain weave is adopted, the mesh number of the copper mesh material is 200 mesh, and the thickness is 0.115mm; The copper wire is composed of the following components in weight percentage: Sn 0.4%, Al 0.09%, B 0.06%, Cr 0.24%, Ni 0.14%, Zn 0.17%, and the rest is Cu and inevitable impurities.

[0026] Example 4 The only difference between this embodiment and embodiment 3 is that in this embodiment, the copper wire is composed of the following components in weight percentage: Sn 0.4%, Al 0.135%, B 0.0875%, Cr 0.14%, Ni 0.14%, Zn 0.17%, and the rest is Cu and inevitable impurities.

[0027] Example 5 The only difference between this embodiment and embodiment 3 is that in this embodiment, the copper wire is composed of the following components in weight percentage: Sn 0.4%, Al 0.1%, B 0.0625%, Cr 0.225%, Ni 0.14%, Zn 0.17%, and the rest is Cu and inevitable impurities.

[0028] Example 6 The only difference between this embodiment and embodiment 3 is that in this embodiment, the copper wire is composed of the following components in weight percentage: Sn 0.4%, Al 0.1%, B 0.1%, Cr 0.15%, Ni 0.14%, Zn 0.17%, and the rest is Cu and inevitable impurities.

[0029] Example 7 The only difference between this embodiment and embodiment 3 is that in this embodiment, the copper wire is composed of the following components in weight percentage: Sn 0.4%, Al 0.15%, B 0.075%, Cr 0.15%, Ni 0.14%, Zn 0.17%, and the rest is Cu and inevitable impurities.

[0030] Example 8 The only difference between this embodiment and embodiment 3 is that in this embodiment, the copper wire is composed of the following components in weight percentage: Sn 0.4%, Al 0.2%, B 0.05%, Cr 0.15%, Ni 0.14%, Zn 0.17%, and the rest is Cu and inevitable impurities.

[0031] Example 9 The difference between this embodiment and embodiment 8 is that in step S3 of this embodiment, the heat treatment includes a first stage heat treatment and a second stage heat treatment; In the first stage of heat treatment, the holding temperature is 450°C and the holding time is 2h. After the holding is completed, it is cooled to room temperature at a cooling rate of 4°C / s; In the second stage of heat treatment, the holding temperature is 950°C and the holding time is 1h. After the holding is completed, it is cooled to room temperature at a cooling rate of 16°C / s.

[0032] Example 10 The difference between this embodiment and embodiment 9 is that in this embodiment, during the first stage of heat treatment, the holding temperature is 450°C, the holding time is 2h, and after the holding is completed, it is cooled to room temperature at a cooling rate of 16°C / s; In the second stage of heat treatment, the holding temperature is 950°C and the holding time is 1h. After the holding is completed, it is cooled to room temperature at a cooling rate of 4°C / s.

[0033] Embodiment 11 The difference between this embodiment and embodiment 9 is that in this embodiment, during the first stage of heat treatment, the holding temperature is 950°C, the holding time is 1h, and after the holding is completed, it is cooled to room temperature at a cooling rate of 4°C / s; In the second stage of heat treatment, the holding temperature is 450°C and the holding time is 2h. After the holding is completed, it is cooled to room temperature at a cooling rate of 16°C / s.

[0034] Example 12 The difference between this embodiment and embodiment 9 is that in this embodiment, during the first stage of heat treatment, the holding temperature is 950°C, the holding time is 1h, and after the holding is completed, it is cooled to room temperature at a cooling rate of 16°C / s; In the second stage of heat treatment, the holding temperature is 450°C and the holding time is 2h. After the holding is completed, it is cooled to room temperature at a cooling rate of 4°C / s.

[0035] Example 13 The difference between this embodiment and embodiment 9 is that in this embodiment, during the first stage of heat treatment, the holding temperature is 900°C, the holding time is 2h, and after the holding is completed, it is cooled to room temperature at a cooling rate of 12°C / s; In the second stage of heat treatment, the holding temperature is 500°C and the holding time is 1h. After the holding is completed, it is cooled to room temperature at a cooling rate of 8°C / s.

[0036] Comparative Example 1 The only difference between this comparative example and Example 1 is that, in this comparative example, the copper wire is composed of the following components in weight percentage: Sn 0.2%, Al 0.06%, Cr 0.14%, Ni 0.12%, Zn 0.14%, and the rest is Cu and inevitable impurities.

[0037] Comparative Example 2 The only difference between this comparative example and Example 1 is that, in this comparative example, the copper wire is composed of the following components in weight percentage: Sn 0.2%, B 0.03%, Cr 0.14%, Ni 0.12%, Zn 0.14%, and the rest is Cu and inevitable impurities.

[0038] Comparative Example 3 The only difference between this comparative example and Example 1 is that, in this comparative example, the copper wire is composed of the following components in weight percentage: Sn 0.2%, Al 0.06%, B 0.03%, Ni 0.12%, Zn 0.14%, and the rest is Cu and inevitable impurities.

[0039] Comparative Example 4 The only difference between this comparative example and Example 1 is that, in this comparative example, the copper wire is composed of the following components in weight percentage: Sn 0.2%, Cr 0.14%, Ni 0.12%, Zn 0.14%, and the rest is Cu and inevitable impurities.

[0040] Comparative Example 5 The only difference between this comparative example and Example 1 is that in this comparative example, the copper wire is composed of the following components in weight percentage: Sn 0.2%, Ni 0.12%, Zn 0.14%, and the rest is Cu and inevitable impurities.

[0041] Experimental Example 1 Electromagnetic Shielding Test The shielding effectiveness of the copper mesh materials prepared in Examples 1 to 13 at 50 MHz was tested with reference to GB / T 30142-2013 "Measurement Method for Shielding Effectiveness of Planar Electromagnetic Shielding Materials". The results showed that the shielding effectiveness could reach 90 to 95 db, which indicates that the copper mesh material prepared in the present invention has good wave absorbing performance.

[0042] Experimental Example 2 Strength Test The tensile strength and yield strength of the copper wires in Examples 1 to 13 and Comparative Examples 1 to 5 were tested using a GL2000 microcomputer-controlled electro-hydraulic servo universal testing machine, wherein the test rate was 0.006 s -1 The final result was the average of the three samples in each group.

[0043] The test results are shown in Table 1 below.

[0044] Table 1 Test results of tensile strength and yield strength

[0045] Comparison between Example 1 and Comparative Examples 1 to 5 shows that the strength of the copper wire can be improved by using the three elements Al, B and Cr together. Comparison between Examples 3 to 4 and Examples 5 to 6 shows that when the weight ratio of the sum of the weights of Al and B to the weight ratio of Cr is 1≤(Al+2B) / Cr≤2, it helps to further improve the strength of the copper wire. Comparison between Examples 6 to 7 and Example 8 shows that when the weight ratio of the sum of the weights of Al and B to the weight ratio of Cr is 1≤(Al+2B) / Cr≤2 and Al / B>2, the strength of the copper wire can be further improved. Comparison between Examples 12 to 13 and Examples 8 to 11 shows that when the heat treatment includes a first-stage heat treatment and a second-stage heat treatment and in the first-stage heat treatment, the holding temperature is 900 to 950°C, the holding time is 1 to 2 hours, and after the holding is completed, it is cooled to room temperature at a cooling rate of 12 to 16°C / s; in the second-stage heat treatment, the holding temperature is 450 to 500°C, the holding time is 1 to 2 hours, and after the holding is completed, it is cooled to room temperature at a cooling rate of 4 to 8°C / s, which can further improve the strength of the copper wire.

[0046] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength microwave-absorbing copper mesh material, woven from copper wires, characterized in that: The copper wire is composed of the following components in weight percentage: Sn 0.2%-0.6%, Al 0.06%-0.24%, B 0.03%-0.135%, Cr 0.14%-0.24%, Ni 0.12%-0.18%, Zn 0.14%-0.2%, and the rest is Cu and inevitable impurities.

2. A high-strength microwave-absorbing copper mesh material according to claim 1, characterized in that: The weight ratio of the sum of the weights of Al and B to the weight of Cr is 1≤(Al+2B) / Cr≤2.

3. A high-strength microwave-absorbing copper mesh material according to claim 2, characterized in that: The weight ratio of the Al to the B is Al / B>2.

4. The method for preparing a high-strength microwave-absorbing copper mesh material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, smelting: weighing raw materials according to the components in weight percentage, smelting, and obtaining copper liquid; S2, casting: the copper liquid is cast to obtain a copper ingot; S3, wire forming: the copper ingot is forged, rolled, heat treated and drawn to obtain copper wire; S4, weaving: the copper wires are weaved to obtain a copper mesh material.

5. The method for preparing a high-strength microwave-absorbing copper mesh material according to claim 4, characterized in that: In step S1, during the smelting, the temperature is 1200-1250° C. and the time is 10-20 min.

6. The method for preparing a high-strength microwave-absorbing copper mesh material according to claim 4, characterized in that: In step S3, during the rolling, the temperature is 680-850°C.

7. The method for preparing a high-strength microwave-absorbing copper mesh material according to claim 4, characterized in that: In step S3, the heat treatment includes a first stage heat treatment and a second stage heat treatment; During the first stage of heat treatment, the holding temperature is 900-950°C for 1-2 hours. After the holding is completed, the material is cooled to room temperature at a cooling rate of 12-16°C / s. During the second stage heat treatment, the holding temperature is 450-500°C, the holding time is 1-2h, and after the holding is completed, it is cooled to room temperature at a cooling rate of 4-8°C / s.

8. The method for preparing a high-strength microwave-absorbing copper mesh material according to claim 4, characterized in that: In step S3, the wire diameter of the copper wire is 0.025-0.1 mm.

9. The method for preparing a high-strength microwave-absorbing copper mesh material according to claim 4, characterized in that: In step S4, during the weaving, the weaving method is plain weave or twill weave.

10. The method for preparing a high-strength microwave-absorbing copper mesh material according to claim 4, characterized in that: In step S4, the mesh size of the copper mesh material is 80-400 meshes and the thickness is 0.05-0.23 mm.